ANTERIOR ARTHRODESIS FOR TUBERCULOSIS OF THE SPINEUSING ZETA INSTRUMENTATION ON LATERAL SIDE (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
This is a prospective study of twelve patients who are diagnosed to have tuberculosis of spine with some form ofneurological deficit. In the present study, the progression of kyphosis and the fate of the bone graft and final outcome overan average twelve month follow up after radical anterior debridement, bone grafting and application of Zeta Instrumentationon the lateral side of the vertebral body is performed. Supplementation with an implant to the procedure of bone graftingafter radical debridement is a good choice as a primary procedure. It was noted that It is easy to place the implant on thelateral aspect of the bodies of the spine. There is no need of a second procedure in the form of posterior instrumentation andposterior fusion at a later date. Can be used by surgeons, where the facilities for pedicular screw fixation are not present.There is no progression of the deformity